Establishment of rat pancreatic endocrine cell lines by infection with simian virus 40. - Niesor, E J (1979)
The feasibility of infection and transformation by SV40 (simian virus 40) of primary cell cultures derived from newborn-rat pancreas was investigated. As judged by the presence of intranuclear SV40 T-antigen, exposure to the virus resulted specifically in infection and transformation of epithelioid (predominantly endocrine) cells. The transformed cells were subcultured (more than 64 passages) and cloned. Culture medium and acid/ethanol extracts of the cells did not contain detectable amounts of immunoreactive insulin after the third subculture. However, inoculation of such SV40-transformed pancreatic cells into immunodeficient rats results in tumours in which insulin production was partially restored through the passage in vivo, since the tumour cells contained and synthesized small amounts of immunoreactive insulin which co-migrated with an insulin marker on gel chromatography. Interestingly, the transformed cells maintained under tissue-culture conditions produced a protein immunologically related to insulin, soluble in aqueous buffer but insoluble in acid/ethanol. This 3000-dalton protein is too large to be a translation product of the rat preproinsulin 9S mRNA. SV40-transformed pancreatic cells might prove useful in the investigation of the factors controlling and maintaining insulin biosynthesis.